KNOWLEDGE, RISK MANAGEMENT, AND TECHNOLOGY AS DETERMINANTS OF STRATEGIC MANAGEMENT - Fitriana Nur Rohmah; Riswanti; Afidah Rozi Anti (Journal of Islamic Management Studies, 2024)
This article reviews the factors in strategic management, namely knowledge, risk management, and technology. This research uses a methodology-based qualitative approach to library research. Using a descriptive approach with analysis through data collection, data reduction, display, and drawing conclusions or verification. The results of this study state that knowledge plays a role in informed decision-making, innovation, and organizational learning. Risk management helps organizations identify threats and opportunities, control risk, and make wise investment decisions. Technology influences strategy management through data analytics, business process automation, and the creation of competitive advantages. Integrating these three factors becomes the key to success in planning and executing business strategies, enabling organizations to achieve their business goals and remain competitive in a competitive global marketplace. Sustainable business success includes achieving financial goals, customer satisfaction, growth, and competitiveness in an increasingly tight market.